2021
DOI: 10.5937/vojtehg69-29512
|View full text |Cite
|
Sign up to set email alerts
|

High-yielding and chemically enriched maize hybrids bred in Serbia: The best basis for super quality feed and food

Abstract: Introduction/purpose: This paper presents the results of several different research studies. The inbred lines ZPPL 146 and ZPPL 159 and the maize hybrids ZP 633, ZP 735, and ZP 737 are primarily intended for human and livestock nutrition. Their selection took about four decades. Methods: Spectral bands were registered using the method of resonant Raman spectroscopy of the leaves of inbred maize lines. These spectral bands indicate the conformational characteristics of not only carotenoid molecules but also oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is known that carotenoid bound to protein complexes collects light to the photosystem II, and is characterized by the intensive spectral band at 960 cm -1 in the Raman spectrum, which particularly differs in the amplitude from bands at 1156 and 1004 cm -1 . Moreover, it has also been observed that the amplitude of the band at 960 cm -1 of the carotenoid Raman spectrum has been significantly smaller than amplitudes of the spectral bands at 1156 and 1004 cm -1 , and that it does not differ in different lines in the chloroplast Raman spectrum, which probably indicates the absence of protein-lipid interactions (Radenović et al, 2021a;Radenović et al, 2021b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that carotenoid bound to protein complexes collects light to the photosystem II, and is characterized by the intensive spectral band at 960 cm -1 in the Raman spectrum, which particularly differs in the amplitude from bands at 1156 and 1004 cm -1 . Moreover, it has also been observed that the amplitude of the band at 960 cm -1 of the carotenoid Raman spectrum has been significantly smaller than amplitudes of the spectral bands at 1156 and 1004 cm -1 , and that it does not differ in different lines in the chloroplast Raman spectrum, which probably indicates the absence of protein-lipid interactions (Radenović et al, 2021a;Radenović et al, 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…It is desirable to analyze the Raman spectrum with all spectral bands for the maize inbred lines studied (M1-3-3Sdms, ZPPL186, and ZPPL225) in the range from 400 to 1600 cm -1 . It was established that the Raman spectra of maize leaf chloroplasts within this range are characterized by high-amplitude bands of carotenoids and low-amplitude bands of cellulose molecules (bands at 1095 cm -1 and 1477 cm -1 correspond to valence oscillations of S -O -S bonds and N -S -H groups of atoms of cellulose molecules, respectively) (Radenović et al, 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…It has at least two aspects. The first refers to the functional role of certain structural parts of the kernel that carry out life functions [18], while the second aspect refers to the quality of structural parts of kernels, and finally to the need for human nutrition [7,19].…”
Section: Resultsmentioning
confidence: 99%
“…Kernels of high yielding, chemically enriched and outstanding quality maize hybrid ZP 633, were used as a material for studying infrared spectra and all spectral bands of different properties: intensity, kinetics and the site of origin. This hybrid is also very suitable for human consumption (standard for nutrition of children, elderly, and in certain cases athletes) [7]. The outstanding quality maize hybrid ZP 633 has been developed at and is the property of the Maize Research Institute, Zemun Polje, Belgrade, Serbia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation